Effects of Organic Pollution on some Fish and Benthic Macroinvertebrate Groups in Rivers Tigris and Diyala at Baghdad Area. - Baghdad Science Journal (مجلة بغداد للعلوم, 2011)
Various activities taking place within the city of Baghdad have significantly contributed to organic pollution in Rivers Tigris and Diyala. The present study aimed to assess some physical, chemical and biological aspects of six sites on Rivers Tigris and Diyala as they flow through the city of Baghdad. Monthly samples were collected for the period January to December, 2005. Marked differences in the physical and chemical characteristics of water were noted between the two rivers’ sites. Average values during the study period of dissolved oxygen, biochemical oxygen demand, particulate organic matter, nitrate, phosphate and total dissolved solids for Tigris and Diyala were 7.8,4.7; 2.4,10.4; 350.1,921.4;7.8,13.9;1.2,4.8;814,2176 mg / l respectively. The populations of two fish species, known to be present in polluted waters Silurus triostegus and Mystus pelusis, were also investigated. The two species markedly differed in their favored sites, and their numbers were significantly correlated with particulate organic matter. Average length and weight of Silurus triostegus and Mystus pelusius were respectively 40.1mm, 56.8gm and 15.3mm, 68.3gm for River Tigris, and 40.5mm, 67.5gm and 17.9mm, 73gm respectively for River Diyala. Average population densities of the major groups of benthic macro invertebrate fauna [Crustaceans, Annelids, Insects and Mollusks] were 1496, 2640, 2574 and 1744 individual/m2 respectively for River Tigris and 463, 2312, 2287 and 1700 individual/m2 respectively for River Diyala. Most invertebrate groups showed positive correlation with particulate organic matter. Despite the severity of organic enrichment in River Diyala, biotic conditions in its sites were rather similar, unlike sites on River Tigris where they significantly differed in many physical, chemical and biotic respects.